A Large Imprinted microRNA Gene Cluster at the Mouse Dlk1-Gtl2 Domain - Seitz, Hervé; Royo, Hélène; Bortolin, Marie-Line; Lin, Shau-Ping; Ferguson-Smith, Anne C.; Cavaillé, Jérôme

(untitled) (Genome Research, 2004)
microRNAs (or miRNAs) are small noncoding RNAs (21 to 25 nucleotides) that are processed from longer hairpin RNA precursors and are believed to be involved in a wide range of developmental and cellular processes, by either repressing translation or triggering mRNA degradation (RNA interference). By using a computer-assisted approach, we have identified 46 potential miRNA genes located in the human imprinted 14q32 domain, 40 of which are organized as a large cluster. Although some of these clustered miRNA genes appear to be encoded by a single-copy DNA sequence, most of them are arranged in tandem arrays of closely related sequences. In the mouse, this miRNA gene cluster is conserved at the homologous distal 12 region. In vivo all the miRNAs that we have detected are expressed in the developing embryo (both in the head and in the trunk) and in the placenta, whereas in the adult their expression is mainly restricted to the brain. We also show that the miRNA genes are only expressed from the maternally inherited chromosome and that their imprinted expression is regulated by an intergenic germline-derived differentially methylated region (IG-DMR) located ∼200 kb upstream from the miRNA cluster. The functions of these miRNAs, which seem only conserved in mammals, are discussed both in terms of epigenetic control and gene regulation during development.